Interações medicamentosas potenciais com benzodiazepínicos em prescrições médicas de pacientes hospitalizados - Viel, Amanda Martins [UNESP]; Ribeiro-Paes, João Tadeu [UNESP]; Stessuk, Talita; dos Santos, Lucinéia [UNESP] (My University, 2014)
The practice of drug combinations is common in hospitalized patients. This practice is often necessary, especially in psychiatric patients, since other comorbidities may occur in parallel with neuropsychiatric disorders. However, this practice may favor the occurrence of drug interactions with consequent increase of different adverse effects. Facing this situation, the present study aimed to evaluate the occurrence of potential drug interactions with benzodiazepines prescribed to hospitalized patients at the Psychiatric Clinic of the Hospital Regional de Assis - SP, in order to generate information that contributes to the effectiveness of the treatment provided to patient. To this end, an analysis of 100 medical prescriptions was performed, in which were evaluated the possibility of drug interactions between the different medications from the class of benzodiazepines concomitantly administered, as well as other classes of drugs. By means of this study, it was verified that the 100 analyzed prescriptions 93 presented the possibility of different pharmacological interactions between benzodiazepine, and with other classes of drugs, totaling 356 possible interactions. Of this total stand out the associations of benzodiazepines with antipsychotics, antihistamines, antiepileptics and antidepressants, which can enhance the expression of numerous adverse effects, highlighted the exacerbation of depressant effect on the central nervous system, with effects that can range from mild clinical manifestation until risk of lethal outcome. In this context, it seeks in this work to contribute to a better understanding, recognition and early or prophylactic intervention in clinical situations arising from interactions between different pharmacological classes of drugs with benzodiazepines.
Potential drug interactions with benzodiazepines in medical prescriptions of hospitalized patients
Keywords: Anxiolytics; Benzodiazepines; Drug interactions; Prescriptions